ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MAHASISWA AKUNTANSI BERKARIR SEBAGAI AKUNTAN PUBLIK DI KOTA BATAM - Neni Marlina Br.Purba (LPPM Universitas Putera Batam, 2022)
Public accounting is seen as one of the most secure professions for now. This study isaims to test and analyze empirically the assessment of financial rewards, professionaltraining, work environment and sosial value on the interests of students in Batam Citychoose career as a public accountant. The method use for the sampling in this study ispurposive sampling method with 1.087 accounting students in Batam City as thepopulation of this research and used 100 accounting students in Batam City as the sampleobtained from the Slovin formula. The sample has been used in this research isacccounting student that on their 5th abd 7th semester. This research collects the data fromquestionnaire and using a Likert scale to measure the questions than tested using anSPSS application to test. This research uses multiple regression analysis. This researchprove that financial reward, professional training and work environment have an influencepositive and significant influence accounting students becoming public accountants. Whilethe social value is negative significant influence career accounting students becomingpublic accountants.